Vine Copula를 활용한 기후변화 시나리오 시간적 상세화 기법 개발 - 유재웅; 권윤정; 박민우; 권현한; Yu, Jae-Ung; Kwon, Yoon Jeong; Park, Minwoo; Kwon, Hyun-Han (KSCE Journal of Civil and Environmental Engineering Research, 2024)
A Copula approach has the advantage of providing structural dependencies for representing multivariate distributions for the hydrometeorological variable marginal distribution involved, however, copulas are inflexible for extending in high dimensions, and satisfy certain assumptions to make the dependency. In addition, since the process of estimating design rainfall under the future climate associated with durations given a return period is mainly analyzed by 24-hour annual maximum rainfalls, the dependency structure contains information only on the daily and sub-daily extreme precipitation. Methods based on bivariate copula do not provide information for other duration's dependencies, which causes the intensity to be reversed. The vine copula has been proposed to process the multivariate analysis as vines consisting of trees with nodes and edges connecting pair-copula construction. In this study, we aimed to downscale under climate change to produce sub-daily extreme precipitation data considering different durations based on vine copula. 일반적으로 수문기상변량의 상관관계를 파악하기 위해서는 Copula 기법을 활용하여 의존관계를 규명하고 있으나, 단순히 Copula 기법을 다변량으로 확장하는 것은 분석결과가 유연하지 않으며 Copula 기법에 대한 수학적인 가정을 확인하여 만족 여부를 판단해야 하는 등 복잡해지는 단점이 있다. 또한, 기존의 이변량 Copula 기법을 활용하여 기후변화모델의 지속시간에 따른 설계강우량을 추정하는 과정은 주로 일별 자료만을 활용하여 분석하므로 24시간 최대강우량에 대한 정보와의 의존관계를 규명하여 추정하는 방법을 채택하고 있다. 그러나, 24시간 최대강우량만을 활용하여 다른 지속시간에 대한 설계강우량을 산정하는 것은 다른 지속시간에 대한 의존관계 정보는 제공되지 않아 지속시간에 따른 강우 강도가 역전되는 현상이 야기되는 원인이다. 따라서, 본 연구에서는 변수간의 쌍구조 관계를 연결하는 Vine Copula 기법을 활용하여 다른 지속 시간에 대한 정보를 반영하여 미래 강우강도의 변화를 전망하고자 한다.